PROTECTIONOF SEISMIC-STABILITYOF LARGE-PANEL BUILDINGS - Kh. Kuldashev; Kh. Ibragimov; B.Mannatov (European Journal of Life Safety and Stability (2660-9630), 2021)
There are presented new decisions of increasing seismic-stability of high-rise large-panel buildings by way active of seismic-protection. Offered new constructive decision of the high-rise building with element active seismic-protection is in type seismic- insulation of slithering belt, located between lower and upper hard part of the building. Given decision is received author’s certificate on invention. For ensuring of seismic-stability buildings in system are provided springy and hard limiters horizontal and vertical displacement. At earthquake in the beginning emerges in work flexible framework, but then sliding belt. Power of the slide of the belt at fluctuation of the framework have an opposite direction so occurs general extinguishing the amplitude of the fluctuations of the framework. Offered decision provides the efficient system anseismic- insulation, that is recommended at construction of the high-rise large-panel buildings, seismicity 7-8 rates.